Root hair abundance impacts cadmium accumulation in Arabidopsis thaliana shoots. (31st January 2018) - Kohanová, Jana; Martinka, Michal; Vaculík, Marek; White, Philip J; Hauser, Marie-Theres; Lux, Alexander
Abstract: Background and Aims: Root hairs increase the contact area of roots with soil and thereby enhance the capacity for solute uptake. The strict hair/non-hair pattern of Arabidopsis thaliana can change with nutrient deficiency or exposure to toxic elements, which modify root hair density. The effects of root hair density on cadmium (Cd) accumulation in shoots of arabidopsis genotypes with altered root hair development and patterning were studied. Methods: Arabidopsis mutants that are unable to develop root hairs ( rhd6 -1 and cpc/try ) or produce hairy roots ( wer/myb23 ) were compared with the ecotype Columbia (Col-0). Plants were cultivated on nutrient agar for 2 weeks with or without Cd. Cadmium was applied as Cd(NO3 )2 at two concentrations, 10 and 100 µm . Shoot biomass, root characteristics (primary root length, lateral root number, lateral root length and root hair density) and Cd concentrations in shoots were assessed. Anatomical features (suberization of the endodermis and development of the xylem) that might influence Cd uptake and translocation were also examined. Key Results: Cadmium inhibited plant growth and reduced root length and the number of lateral roots and root hairs per plant. Suberin lamellae in the root endodermis and xylem differentiation developed closer to the root apex in plants exposed to 100 µm Cd. The latter effect was genotype dependent. Shoot Cd accumulation was correlated with root hair abundance when plants were grown in the presence of 10 µm Cd, but not when grown in the presence of 100 µm Cd, in which treatment the development of suberin lamellae closer to the root tip appeared to restrict Cd accumulation in shoots. Conclusions: Root hair density can have a large effect on Cd accumulation in shoots, suggesting that the symplasmic pathway might play a significant role in the uptake and accumulation of this toxic element.